Know Yourself, Achieve Your Dreams: Psychoeducational Training on Self-Concept and Future Planning for Adolescents - Tri Handayani, Fina; Nanda Pratama, Haichal; Irsyad Fadzly, Ahmad; Khusniyah, Mir'atul; Alifiah Putri, Intan; Qur'aniyah, Millatil; Nor Halizah, Siti; Mufidah, Wardatul (Edumedia Solution, 2025)
During adolescence, the development of personal identity and self-image is crucial. In this phase, adolescents are searching for their identity, their vision of the future, and what they want. The